Nutritional peculiarities during the prenatal period and physical status of the offspring: a pilot experimental study - Araminaitė, V.; Šimkūnaitė-Rizgelienė, R.; Žalgevičienė, V.; Bukelskienė, V.; Tutkuvienė, J. (Acta medica Lituanica, 2013)
Nutrition in uterus has a significant influence on the formation of metabolic phenotype in offspring generations. The objective of this study was to investigate maternal nutrition and the changes in body weight at few generations of rat offspring. Materials and methods. 12 maternal rats and 121 offspring rats were used in the study. Mature female Wistar rats were divided into 3  groups with respect to nutritional restriction (one control and two experimental groups). Rats from the first experimental group (1  EG) were 50  percent food-restricted one month prior and during the pregnancy; rats from the second experimental group (2 EG) were 50 percent food-restricted exclusively one month prior to the pregnancy. After weaning all the pups were fed with control diet, weighted weekly, observed and evaluated for the morphological indices of metabolic stress. Results and conclusions. Maternal nutritional restriction in pre-pregnancy and pregnancy may alter the physical status and behaviour of the offspring: the reactions differ in both sexes; the alterations depend on the time window of exposure. There were no weight-related differences between groups in body weight of female offspring rats during the all time periods of the study. The first generation 1 EG male offsprings were the heaviest; the tendency for a greater than control group weight was also observed at the second generation up till the early reproductive period. The 2nd generation 2 EG male rats were the heaviest and exhibited some evident markers of chronic diseases.
Keywords: nutritional deprivation; pregnancy; growth programming; thrifty phenotype